Enantioselective Conjugate Additions of α-Amino Radicals via Cooperative Photoredox and Lewis Acid Catalysis - Espelt, Laura Ruiz (J Am Chem Soc, 2015)
[Image: see text] We report the highly enantioselective addition of photogenerated α-amino radicals to Michael acceptors. This method features a dual-catalyst protocol that combines transition metal photoredox catalysis with chiral Lewis acid catalysis. The combination of these two powerful modes of catalysis provides an effective, general strategy to generate and control the reactivity of photogenerated reactive intermediates.